Controlled synthesis of Fe3O4@ZIF-8 nanoparticles for drug delivery. Issue 46 (30th October 2018) - Chen, Guihuan; Yu, Bing; Lu, Chenghao; Zhang, Haohao; Shen, Youqing; Cong, Hailin
Abstract : A novel one-pot synthetic method is introduced to produce Fe3 O4 @ZIF-8 NPs, which are proven to have potential applications as drug delivery models. Abstract : Encapsulating well-defined nanoparticles (NPs) into ZIF-8 to form core–shell structures not only can minimize the drawbacks and maximize the advantages of the disparate components but also may provide synergistic functionality. This work presents novel one-pot synthetic methods to produce Fe3 O4 @ZIF-8 NPs. Moreover, the morphology of Fe3 O4 @ZIF-8 NPs can be easily controlled by changing the synthesis conditions (time, temperature, and dosage). The as-obtained Fe3 O4 @ZIF-8 NPs have good dispersibility and a large specific surface area and they are proven to have potential applications as drug delivery models with good biocompatibility, high drug loading and good pH responsiveness.